Private property rights, government interventionism and welfare economics - Ivan Jankovic; Walter Block (Review of Economic Perspectives, 2019)
We develop a critique of government interventionism based on the Misesian calculation argument against socialism. If private property rights and relative prices based on supply and demand are necessary for successful economic coordination, then conventional market failure theories cannot be sustained. Government interventionism based on the idea of correcting "market failures" is analytically just a milder form of socialist central planning. Between the two, there are only differences in degree, not in kind. We criticize several public choice and law and economics scholars for disregarding this Misesian angle in their market failure theories. In our view they are reducible to arguments based on a fallacious political economy while perpetuating false neoclassical economic analysis of market failure theorists. We claim that government interventionism is just a milder form of socialist central planning. Therefore, the traditional arguments against the efficiency of central planning also apply to government interventions aiming at fixing market failures. In particular, we maintain that governments face the "knowledge problem", which means that they cannot determine the optimal allocation of resources. In section two of this paper we discuss market failure and economic calculation. Section three is given over to our claim that the "Nirvana fallacy" is itself fallacious. The burden of section four is to address Coase and consequences. We conclude in section five.
Keywords: A13; 330; Government failure; market failure; prices; private property rights; subjectivism; socialism; public choice